Do Collared Peccaries Negatively Impact Understory Insectivorous Rain Forest Birds Indirectly Via Lianas and Vines?. (7th October 2015) - Michel, Nicole L.; Carson, Walter P.; Sherry, Thomas W.
Abstract: Tropical rain forest understory insectivorous birds are declining, even in large forest reserves, yet the mechanisms remain unclear. Abundant large mammals can reshape forest structure, which degrades foraging microhabitat. We used six sites in Nicaragua, Costa Rica, and Panama with varying collared peccary ( Pecari tajacu ) density to test three linked hypotheses: (1) locally declining understory insectivores forage preferentially in liana tangles; (2) vine and liana density, cover, and frequency of dense tangles are lower in the presence of abundant collared peccaries; and consequently (3) abundant collared peccaries are associated with reduced understory insectivorous bird abundance. Three insectivores that declined at La Selva preferentially foraged in liana tangles: Checker‐throated Antwren ( Epinecrophylla fulviventris ), Dot‐winged Antwren ( Microrhopias quixensis ), and Ruddy‐tailed Flycatcher ( Terenotriccus erythrurus ). Vine density, liana cover, liana tangle frequency, and forest cover were lower in the presence of collared peccaries relative to experimental mammal exclosures, with the greatest differences at La Selva Biological Station, Costa Rica. Across sites, five of seven vine and liana measures showed negative, curvilinear relationships with peccary densities. Vine and liana measures peaked at sites with intermediate peccary density, and were low at La Selva. Structural equation models suggest negative indirect effects of the collared peccaries on focal bird densities, mediated by vine and liana density, cover, or tangle frequency. Forest area and rainfall affected both lianas and birds, but collared peccaries also contributed to the reduced abundance of understory insectivores. Indirect effects such as that suggested here may occur even in large, protected forest reserves where large mammal communities are changing.